Dynamic Response and Safety Control of Newly Poured Secondary Lining Concrete under Large Section Tunnel Blasting-A Case Study of Longnan Tunnel of Ganshen High-speed Railway - Xiong, Linghao; Zhou, Chuanbo; Jiang, Nan; Wang, Teng; Meng, Xianzhong (Periodica Polytechnica Civil Engineering, 2022)
The age of newly poured concrete is short, the cementation between aggregates is weak. At this time, the vibration will affect its performance. The secondary lining concrete newly poured in the tunnel is close to the work face and is susceptible to blasting vibration during construction. In order to study the safety threshold of blasting vibration velocity of newly poured secondary lining concrete in tunnels, the finite element model is established in ANSYS with the large-section Longnan tunnel project as an example. The attenuation law of vibration velocity in three directions of secondary lining under blasting load was analyzed by combining field blasting monitoring with numerical simulation, and the reliability of numerical simulation was verified. Through the numerical simulation results, the vibration velocity and von mises stress distribution of the newly poured secondary lining concrete of the tunnel are analyzed; combined with the dynamic tensile strength theory of concrete, the safety threshold of vibration velocity of newly poured secondary lining concrete of tunnel based on numerical calculation is established; through the indoor vibration test, taking the compressive strength and acoustic velocity of concrete as the indexes, the safety threshold of blasting vibration velocity of newly poured secondary lining concrete of tunnel based on shaking table test is obtained. Combined with the results of numerical simulation and vibration test, the safety threshold of blasting vibration velocity of newly poured secondary lining concrete in large-section tunnels is obtained, and the standard in this field is improved.